2018
DOI: 10.1504/ijbpim.2018.10013982
|View full text |Cite
|
Sign up to set email alerts
|

Deriving organisational business process change factors using the hierarchical elicitation workshop

Abstract: in 2011. He is currently a doctoral researcher at Griffith University in the area of business process change. His current research interests include business process management, business process change, regulatory policy implementation and computational models and governance frameworks. Steve Drew AbstractThe hierarchical elicitation workshop is a new initiative designed and developed to address common shortcomings in business process change initiatives in organisations, particularly those with tight temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The QAWs is designed to accomplish the Architecture Trade-off Analysis Method to define an organisation's needs and determine substantial quality attributes to understand the system's architecture structure and define stakeholder relationships. The HCMS framework was constructed by eliciting decision information from each organisational level from the top-down, using a newly developed methodology by the researchers called HCMS Elicitation Workshop (HEW) (Alrabiah & Drew, 2018). Figure 2 summarises the phases and the sequential process steps used to elicit the processes to determine the HCMS.…”
Section: Hierarchical Change Management Structure (Hcms) Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…The QAWs is designed to accomplish the Architecture Trade-off Analysis Method to define an organisation's needs and determine substantial quality attributes to understand the system's architecture structure and define stakeholder relationships. The HCMS framework was constructed by eliciting decision information from each organisational level from the top-down, using a newly developed methodology by the researchers called HCMS Elicitation Workshop (HEW) (Alrabiah & Drew, 2018). Figure 2 summarises the phases and the sequential process steps used to elicit the processes to determine the HCMS.…”
Section: Hierarchical Change Management Structure (Hcms) Frameworkmentioning
confidence: 99%
“…Another advantage is the ability to evaluate alternatives that can promote knowledge and trust in the workplaces. The model is derived from decision trees and an analytical hierarchical process (Alrabiah & Drew, 2018), and is tailored to address this problem area. It is suggested that this framework would allow organisations and practitioners to execute and implement BPCD efficiently and systematically.…”
Section: Practical Findingsmentioning
confidence: 99%
See 1 more Smart Citation